Understanding TikTok Users : How FoMO and TikTok Engagement Affect Self-Control - Gita Maharani; Farid Imam Kholidin; Agung Tri Prasetia; Gita Maharani; Farid Imam Kholidin (Universitas Negeri Malang, 2025)
Currently, technological developments are widely used by people to help their daily activities. With the development of technology, social media is also developing among people, both young and old. This study aims to solve the phenomenon of FoMO problems and the intensity of TikTok use on self-control in adolescents in Sungai Penuh Village. Therefore, the study can be said to be unique from previous studies because, first, this study adds a new variable, namely FoMO, which is continuous with the variable of the intensity of TikTok use and self-control and has not been researched by previous research, the second can support parents in supervision and help adolescents manage their daily time effectively. The research method chosen is the Survey Research method using a descriptive quantitative approach. The sample used in this study focused on adolescents in Sungai penuh village, but the size of this sample had to be adjusted to the purposive sampling technique. FoMO (Fear of Missing Out) and the intensity of TikTok use indirectly have a significant effect on adolescent self-control in Sungai Penuh village, Indonesia.